Comparison of microvascular decompression and percutaneous balloon compression efficacy in patients with V2 idiopathic trigeminal neuralgia - Ji, Ye; Wang, Junwu (Frontiers in Neurology, 2024)
Objective This study aims to compare the efficacy and long-term prognosis of microvascular decompression (MVD) versus percutaneous balloon compression (PBC) in patients with idiopathic V2 (maxillary branch) trigeminal neuralgia. Methods We retrospectively analyzed the clinical information and follow-up data of patients who underwent surgical treatment for V2 idiopathic trigeminal neuralgia from January 2020 to January 2023. A total of 58 patients were included in the MVD group and 99 in the PBC group. All surgeries were performed by two physicians at the same center, with follow-up conducted by a separate, trained researcher. We compared the initial versus 12-month postoperative pain relief rates (scored using the BNI), surgical complications, and described pain relief rates after long-term follow-up in both groups using Kaplan–Meier analysis. Results The study included a total of 157 patients (MVD 58, PBC 99). The median age of patients in the MVD group was lower than that in the PBC group (58 [51–65] vs. 63 [58–69], p = 0.002). There was no significant difference between the two groups in terms of pain relief rates initially after surgery and at 12 months (p = 0.521, p = 0.713). However, the MVD group had significantly better outcomes regarding postoperative facial numbness (p < 0.0001), masticatory weakness (p = 0.0017), and other complications (p = 0.04). Kaplan–Meier analysis showed that MVD provided a longer duration of pain relief than PBC (p = 0.0323), with most recurrences in both groups occurring within 1–2 years after surgery. Conclusion There were no significant differences in significant pain relief rates between the two groups initially after surgery and at 12 months. However, the MVD group showed a clear advantage over PBC regarding postoperative facial numbness, masticatory weakness, and other complications; moreover, Kaplan–Meier analysis revealed that MVD offers a longer duration of pain relief for patients.